Health information needs of couples undergoing assisted reproductive techniques - Masoomeh Latifi; Leili Allahbakhshian; Fatemeh Eini; Nader Alishan Karami; Mohammed Nasser Al-Suqri (Wolters Kluwer Medknow Publications, 2022)
Background: Couples undergoing Assisted Reproductive Techniques (ART) come across various information needs. This study aimed to identify the health information needs of couples undergoing ART. Materials and Methods: The methodology of the present applied study was qualitative and the research method was conventional qualitative content analysis performed with the participation of 25 infertile couples under ART. The study took nine months (July 2020 to March 2021). The samples were objectively screened based on the criteria from the couples referred to the infertility center affiliated to Hormozgan University of Medical Sciences (Public) and Ome-Leila Specialized infertility clinic (Private) in Bandar Abbas (Iran). Data collection was performed by semi-structured interviews. The typical content analysis method was used in this research. Data analysis was carried out based on coding by the use of MAXQDA a software for qualitative and mixed methods data analysis. Results: Information needs of couples under ART were categorized into three main categories and ten subcategories: 1) main cause of infertility [feminine or masculine cause, and etiology (nature and origin)], 2) treatment of infertility [identifying ART, treatment success rate, complications and risks (outcomes) of the treatment method, and treatment duration], and 3) healthcare [advice on medication, healthy nutrition (diet), sexual relations, and daily routine]. Conclusions: The results of this study emphasize that the country's health officials, especially those in charge of the healthcare of infertile couples under ART, must necessarily pay more attention to meeting the needs of this group of people in society.